Coxsackievirus A24 variant associated with acute hemorrhagic conjunctivitis outbreak in Bhutan, 2023 - Sonam Gyeltshen; Tshering Dorji; Kunzang Dorji; Sonam Wangchuk; Dorji Tshering; Yongyuth Poolpanichupatam; Piyawan Chinnawirotpisan; Wudtichai Manasatienkij; Kathryn A. McGuckin Wuertz; Aaron R. Farmer; Chonticha Klungthong (Scientific Reports)
Abstract In 2023, Bhutan detected an outbreak of acute hemorrhagic conjunctivitis (AHC) in southern and central regions, coinciding with similar outbreaks reported in South and Southeast Asia. Laboratory results from clinical specimens were initially inconclusive in identifying the etiological agent. To address this, 18 clinical samples, comprising conjunctival swabs and throat/nasal swabs from nine patients were collected and sent to WRAIR-AFRIMS for further analysis. Specimens were tested using multiplex real-time RT-PCR (Fast-track respiratory 21 kit, FTD21) and hybrid-capture-based next-generation sequencing (NGS) with the Illumina Viral Surveillance Panel. FTD21 testing identified human adenovirus, human bocavirus, influenza A, enterovirus, and/or human rhinovirus in 10/18 specimens (56%). A higher detection rate was observed in conjunctival specimens (78%, 7/9) compared to throat/nasal specimens (33%, 3/9) from the same patients, highlighting the increased sensitivity of conjunctival samples in identifying causative agents of conjunctivitis. Further assessment by NGS detected only coxsackievirus A24 variant (CVA24v) genotype IV in 9/17 specimens (53%), with detection primarily from conjunctival samples. Phylogenetic analyses of CVA24v VP1 sequences revealed genetic distinctions in the 2023 isolates compared to prior outbreaks from 2002–2017, suggesting re-emergence driven by novel genetic mutations. These findings suggest that conjunctival samples are more reliable for detecting the etiological agent in AHC outbreaks compared to throat/nasal swabs. Additionally, the identification of a novel strain of CVA24v genotype IV underscores the importance of genomics.